Transparent Vessels?: What Organ Donors Should Be Allowed to Know about Their Recipients. Issue 1 (12th April 2013) - Dees, Richard H.
Abstract : A live organ donor needs to be informed carefully about the risks and benefits of her donation for both herself and her recipient, but a key ethical question is how much the donor is allowed to know about the recipient. To decide this question, we must first decide whether, out of respect for autonomy, the donor should decide how much she wants to know, or whether the transplant team, as the professionals, should decide what information is relevant to the donor's decision. I argue that the transplant team should control the process. While the donor has the right to know enough about her recipient to assess the risk to herself and the prospects for a successful donation, she is not entitled to any further information, no matter how much she wants it. In particular, I argue that donors are not entitled to information that has not been shown to affect outcomes, but that they should be told if a recipient is HIV or that he has rejected a previous organ due to non‐compliance. Donors have a right to make decisions with all the information they need, but recipients need not make their lives completely transparent.